Особливості росту і розвитку однорічних сіянців видів роду Rhododendron L. в умовах дендропарку “Софіївка” НАН України - Vegera, L.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
An investigation results of growth and development characteristics of 20 species of the genus Rhododendron L., which were handled under the introduction conditions of Dendrological Park Sofiyivka of the NAS of Ukraine are given.